1999
DOI: 10.1080/000368499323940
|View full text |Cite
|
Sign up to set email alerts
|

On the gap between payment card and closed-ended CVM-answers

Abstract: The paper presents contingent valuation (CV) estimates of benefits provided by a proposed 'Kalkalpen' National Park in Austria. Although descriptive results of welfare measures are presented, the focus of the paper is on methodological questions concerning the analysis of CV answers. Evidence is given regarding the difference between payment card (PC) answers and closed-ended question formats. Based on different estimation models for CV questions substantial differences are found between closed-ended and payme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Among the group of 1449 respondents who were not prepared to pay the lowest bid amount 1223 persons explicitly stated a zero willingness to pay. Since the spike model takes these zero answers into account a better approximation of the WTP-distribution function can be achieved (see [19]). …”
Section: Estimation Proceduresmentioning
confidence: 99%
“…Among the group of 1449 respondents who were not prepared to pay the lowest bid amount 1223 persons explicitly stated a zero willingness to pay. Since the spike model takes these zero answers into account a better approximation of the WTP-distribution function can be achieved (see [19]). …”
Section: Estimation Proceduresmentioning
confidence: 99%
“…The historical date value is typically the highest bond value issued. Although some researchers consider the payment card format problematic (Hackl and Pruckner 1999), others note its resurgence (Carson and Groves 2011). A payment card format will be more appropriate when there are more than two alternatives.…”
Section: Questionnaire and Variablesmentioning
confidence: 99%
“…OE and PC) than for the methods inferring WTP from choices. In addition a number of studies have shown that DC produces higher WTP estimates than OE (Brown et alRyan and Watson, 2009) as well as higher valuations than the PC approach (Holms and Kramer, 1995;Hackl and Pruckner, 1999). Further, several studies have compared OE and PC (Donaldson et al, 1997;Whynes et al, 2003;Lopez-Martin et al, 2008).…”
mentioning
confidence: 99%